2006
DOI: 10.1128/jb.01370-06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proline Reduction in the Nosocomial Pathogen Clostridium difficile

Abstract: Clostridium difficile, a proteolytic strict anaerobe, has emerged as a clinically significant nosocomial pathogen in recent years. Pathogenesis is due to the production of lethal toxins, A and B, members of the large clostridial cytotoxin family. Although it has been established that alterations in the amino acid content of the growth medium affect toxin production, the molecular mechanism for this observed effect is not yet known. Since there is a paucity of information on the amino acid fermentation pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
149
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 52 publications
3
149
0
Order By: Relevance
“…12 Furthermore, it was shown that Hyp can induce the expression of an enzyme responsible for Pro reduction in C. difficile . 13 In contrast to the characterized pathway for Pro reduction (Fig. 2A), the enzymes and downstream metabolites involved in Hyp fermentation had not been identified until our work.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…12 Furthermore, it was shown that Hyp can induce the expression of an enzyme responsible for Pro reduction in C. difficile . 13 In contrast to the characterized pathway for Pro reduction (Fig. 2A), the enzymes and downstream metabolites involved in Hyp fermentation had not been identified until our work.…”
Section: Introductionmentioning
confidence: 78%
“…The presence of this pathway in the order Clostridiales was notable given that anaerobic metabolism of Hyp was first observed in Clostridiales. 13 These organisms carry out Stickland fermentation wherein pairs of amino acids are used as electron donors and acceptors in energy metabolism. 12 It was known as early as 1934 that Pro and Hyp can be used as electron acceptors in such fermentations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations